COMPARATIVE EVALUATION OF PHOTODYNAMIC AND LASER TEETH WHITENING - Ф. А. Валиева; Ф. Х. Ирсалиева (Galaxy International Interdisciplinary Research Journal, 2023)
It is known that a full-fledged personality and successful promotion on the career ladder, as well as the psyche - emotional state depends on the pleasant appearance of a person. The presence of certain cosmetic imperfections leads to a decrease in a person's self-confidence. One of these disadvantages is tooth discoloration. Elimination of such deficiencies is carried out by teeth whitening. However, after whitening, patients complain of increased tooth sensitivity and inflammation mucous membrane of the alveolar ridge. In connection with this, The scientific work studies the level of pro and anti-inflammatory cytokines of saliva before and after professional teeth whitening. Cytokine levels indicate that photodynamic whitening causes less inflammation than laser teeth whitening.